Zastosowanie estymacji pośredniej w analizie zróżnicowania struktury gospodarstw domowych w Polsce według klasy miejsca zamieszkania - Gołata, Elżbieta (Indirect Estimation in the Analysis of Territorial Differentiation of Household Structure in Poland, 2007)
The aim of the study was to analyse territorial differentiation of the household structure according to its size measured by the number of people. The methodological purpose of the research was to examine the properties of indirect estimators of demographic variables represented by the fraction of one person households. Cognitive character is of a twofold dimension. Primarily this is to evaluate the properties of indirect estimators when applied to Household Budget Survey data. On the other hand results provided confirm the hypothesis of a significantly greater differentiation of single person fraction due to the type of the place of residence within regions, not only between voivodships but in much greater extend owing to.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 533-541